Testing of Performance: International Versus Domestic Portfolio - Christine Adi Njotosutikto; Putu Anom Mahadwartha (Program MM Universitas Surabaya, 2020)
This research investigates performance of portfolio with international portfolio and domestic portfolio. Buttler (2012) and Solnik (1974) explained that diversification of international portfolio will reduce risk of portfolio better than domestic portfolio. To measure performance of portfolio this research uses Treynor, Sharpe and Jensen Alpha. This research uses single index model to formed optimal international and domestic portfolio. Test showed that international portfolio have a better performance than domestic portfolio based on Treynor and Sharpe measurement. However, domestic portfolio have a better performance than international portfolio in higher return (Jensen measurement) and high risk.